2018
DOI: 10.1111/jam.13726
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant ApxIV protein enhances protective efficacy againstActinobacillus pleuropneumoniaein mice and pigs

Abstract: The addition of ApxIV to the multicomponent vaccine could enhance homologous and heterologous protection in mice and pigs, respectively, against challenge by A. pleuropneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…Previous studies have shown that herbal additives can change the composition of intestinal bacterial communities of fish (Büyükdevecia et al, 2018;Meng et al, 2019;Wu, Yeh, Hsueh, Yang, & Chu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that herbal additives can change the composition of intestinal bacterial communities of fish (Büyükdevecia et al, 2018;Meng et al, 2019;Wu, Yeh, Hsueh, Yang, & Chu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Current commercial vaccines cannot provide complete protection because the fixed antigen that induce complete immune protection have not been identified (Rycroft and Garside 2000). Some scholars have found that the recombinant ApxIV protein combined with inactivated APP1, known as a multicomponent vaccine, has a good protective effect against both homologous and heterologous A. pleuropneumoniae (Wu et al 2018). In this study, the immunization with the combined vaccine addressed the defects of inactivated A. pleuropneumoniae and RTA protein alone, reducing the clinical symptoms and improving the survival rate of A. pleuropneumoniae-infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…There are 18 serovars of A. pleuropneumoniae (Bosse et al 2018;Liu et al 2018), and the lack of cross immunoprotection among the major serovars has slowed the development of a vaccine. At present, research on an A. pleuropneumoniae vaccine has focused on the pilus protein (Sadilkova et al 2012), lipopolysaccharide (Li et al 2018), outer membrane protein (Xie et al 2016), adhesion (Zhou et al 2013) and A. pleuropneumoniae toxin (Apx) exotoxin (Wu et al 2018), which are involved in colonization, maintenance, lesion induction and host defense escape (Chiers et al 2010). Apx toxins can be divided into four types, Apx I-IV; Apx IV exists in all serovars of A. pleuropneumoniae strains (Schaller et al 1999) and is necessary for virulence (Liu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…pleuropneumoniae (Wu et al 2018). In this study, the immunization with the combined vaccine addressed the defects of inactivated A. pleuropneumoniae and RTA protein alone, reducing the clinical symptoms and improving the survival rate of A. pleuropneumoniae-infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…are 18 serovars of A. pleuropneumoniae (Bosse et al 2018;Liu et al 2018), and the lack of cross immunoprotection among the major serovars has slowed the development of a vaccine. At present, research on an A. pleuropneumoniae vaccine has focused on the pilus protein (Sadilkova et al 2012), lipopolysaccharide (Li et al 2018), outer membrane protein (Xie et al 2016), adhesion (Zhou et al 2013) and A. pleuropneumoniae toxin (Apx) exotoxin (Wu et al 2018), which are involved in colonization, maintenance, lesion induction and host defense escape (Chiers et al 2010). Apx toxins can be divided into four types, Apx I-IV; Apx IV exists in all serovars of A. pleuropneumoniae strains (Schaller et al 1999) and is necessary for virulence (Liu et al 2009).…”
mentioning
confidence: 99%